Responsiveness to curcumin intervention is associated with reduced aortic stiffness in young, obese men with higher initial stiffness. (February 2017) - Campbell, Marilyn S.; Berrones, Adam J.; Krishnakumar, I.M.; Charnigo, Richard J.; Westgate, Philip M.; Fleenor, Bradley S.
Highlights: CurQfen®, a novel curcumin compound, reduces brachial pulse pressure in obese men. Aortic stiffness was reduced by CurQfen® in subjects with increased baseline values. Interleukin-13 is inversely related to aortic stiffness in CurQfen® responders. Abstract: Obesity results in greater aortic stiffness assessed by carotid-femoral Pulse Wave Velocity (cfPWV), which is an independent predictor of cardiovascular (CV) events. We hypothesized that a novel curcumin formulation with enhanced bioavailability, CurQfen®, would reduce cfPWV and inflammation in young, obese men. In the present placebo-controlled pilot study, 22 obese subjects (BMI ⩾ 30.0 kg/m 2 ) were randomized into placebo (n = 11, BMI = 33.18 ± 3.38 kg/m 2 ) and curcumin (n = 11, BMI = 33.29 ± 3.69 kg/m 2 ) supplemented groups. When CurQfen® was supplemented at 500 mg/day for 12 weeks, it was found that individuals who did respond to the treatment (n = 6) entered the study with higher baseline cfPWV versus those who did not respond (n = 5) (6.81 ± 0.83 m/s v. 5.84 ± 0.41 m/s, p = 0.045, group by time interaction). The curcumin responders also had increased plasma IL-13 concentrations (p = 0.018, 12 weeks v. baseline). These findings suggest CurQfen curcumin has potential to de-stiffen arteries in young, obese men with greater aortic stiffness.